Comparison of disc brake pads for truck front wheels based on SAE standard experiments - Topuz, Polat; Comert, Zekeriya Yasar; Topuz, Ahmet (WALTER DE GRUYTER GMBH, 2025)
In this study, trials of disc brake pads, which have different compositions and are used in the front brake systems of trucks, were carried out by SAE-J 661 (Brake Lining Quality Test Procedure), SAE-J 866 (Friction Coefficient Identification and Environmental Marking System for Brake Linings), and SAE-J 2975 (Measurement of Copper and Other Elements in Brake Friction Materials) standards. As a result of the experiments, the superiorities or weaknesses of the brake pads relative to each other were evaluated. In the experimental studies, first, EDS (energy dispersive spectroscopy) analyses were carried out with the help of scanning electron microscopy (SEM) and XRF (X-ray fluorescence) analyses to determine the compositions of three different disk brake pads. After the brake pad compositions were determined, friction-wear tests were carried out following the standards. Apart from these, TG (thermogravimetric) analyses, hardness, density, and internal shear strength measurements were carried out.
Keywords: truck; disk brake pad; composition; friction-wear test; TG analysis; FRICTION; WEAR; Materials Science